Islamic Education Management Paradigm: A Prophetic Perspective - Husni, Husni; Munawar, Muhamad Aris; Nurjanah, Nisa (Bestari, 2022)
This study seeks to elucidate the concept and paradigm of delivering education following the Hadith and Traditions of the Prophet Muhammad. This study employs the method of thematic literature review, wherein the researcher reads, examines, analyzes, and synthesizes the hadiths of the Prophet Muhammad, particularly those about education and education administration. Included among the primary sources are hadith texts. According to the study's findings, there are multiple paradigms for implementing Islamic education. These paradigms include the paradigm of systemic-based education; the paradigm of implementing education based on precision, direction, and discipline; the paradigm of administering justice-based education; the paradigm of good-based education administration; the paradigm of providing education based on belief and not doubt; the paradigm of providing benefit-based education; and the paradigm of providing education based on the principles of humanism values. The seven paradigms of education implementation are derived from authentic, credible, and reliable hadiths, per the hadith of the Prophet Muhammad.